Tea in cardiovascular health and disease: a critical appraisal of the evidence - Klaus W. Lange (Food Science and Human Wellness)
ABSTRACT: The findings of various epidemiological studies, interventions using randomized controlled trials and mechanistic experiments have suggested a protective role of tea and its bioactive components in cardiovascular health. The potential of tea in the prevention of cardiovascular diseases (CVDs) has therefore attracted increasing research interest. Polyphenols, in particular ﬂavonoids, found in both green and black tea, have been suggested to play a primary role in the reduction of CVD risk. While promising results regarding the effects of tea on blood pressure and other CVD-related biomarkers have been found in preclinical experiments, the effects demonstrated in human studies are modest and less satisfactory. This discrepancy may be explained, at least in part, by different research strategies used in human and animal research. However, since tea is globally one of the most commonly consumed beverages, even small beneficial effects in humans may shift the population distribution of CVD risk, with major implications for public health. However, research conducted to date does not yield sufficiently robust evidence to allow a recommendation as to an optimal level of tea consumption as an element of health policies seeking to prevent hypertension and improve cardiovascular health.